BIOM-05. THE HER2 FLIP: HER2 AMPLIFICATION OF TUMOR CELLS IN THE CEREBROSPINAL FLUID (CSF-TCS) OF PATIENTS WITH SOLID TUMOR LEPTOMENINGEAL METASTASIS. (14th November 2022) - Kumthekar, Priya; Youssef, Michael; Blondin, Nicholas; Azadi, Amir; Piccioni, David; Glantz, Michael; Carillo, Jose; Sharma, Akanksha; Avgeropoulos, Nicholas; Makar, Sherif; Blouw, Barbara; Natasha, Anna; et al.
Abstract: INTRODUCTION: Patients with leptomeningeal metastasis (LM) have limited treatment options and a poor outcome. However, they may benefit from targeted therapy. LM patients with HER2-positive primary breast cancer treated with IT trastuzumab demonstrated clinical benefit (Malani, 2020), and improved PFS (Figura, 2019). HER2 amplification in the primary and metastatic tumors can be divergent. Biocept's CNSide TM is a CLIA validated test that can detect CSF tumor cells (CSF-TCs) and interrogate those cells with FISH and NGS. We analyzed HER2 amplification on CSF-TCs in LM patients with breast cancer, non-small cell lung cancer (NSCLC) and upper GI cancer. METHODS: CSF was collected from patients with suspected or confirmed LM with breast cancer (N =134 patients), NSCLC (Nf28 patients) or upper GI cancer (Nf2 patients). CSF TCs were tested for HER2 amplification by FISH using CNSide. RESULTS: HER2 amplification in CSF-TCs was detected in 46% (76/164) of all patients. Of the breast cancer patients, 37% (49/134) flipped HER2 status in the LM tumor, 38% (41/108) switched from a HER2 negative or equivocal primary tumor to HER2 positive CSF-TCs, and 27% (7/26) from a HER2 positive primary tumor to HER2 negative CSF-TCs. For the NSCLC patients, 50% (14/28) showed HER2 amplification on the CSF-TCs. For the upper GI cancer patients, HER2 amplification in CSF-TCs was detected in both patients, one patient had an equivocal HER2 primary tumor and HER2 positive CSF-TCs. CONCLUSION: HER2 amplification was detected in a substantial fraction of CSF-TCs from patients with LM from breast, upper GI, and NSCL cancers. This finding may have important therapeutic (justifying the use of intra-CSF trastuzumab), prognostic (HER2 positivity in NSCLC is associated with poorer prognosis and a higher frequency of CNS metastases) and pathophysiologic implications (a potential role of HER2 amplification in the genesis of CNS metastases). Additional investigations are underway.